2002
DOI: 10.1152/ajprenal.00220.2000
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral membrane Cl-, Na+-, and K+-coupled base transport mechanisms in rat MTALH

Abstract: Mechanisms involved in basolateral HCO[Formula: see text] transport were examined in the in vitro microperfused rat medullary thick ascending limb of Henle (MTALH) by microfluorometric monitoring of cell pH. Removing peritubular Cl− induced a cellular alkalinization that was inhibited in the presence of peritubular 4,4′-diisothiocyanostilbene-2,2′-disulfonic acid (DIDS) and blunted in the absence of external CO2/HCO[Formula: see text]. The alkalinization elicited by removing peritubular Cl−persisted in the bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…In two studies using basolateral membrane vesicles isolated from a purified MTAL tubule suspension, we previously demonstrated that the main basolateral HCO 3 Ϫ efflux pathway in MTAL cells is via Cl Ϫ /HCO 3 Ϫ exchange activity attributable to AE2 (12,13). An additional study from our laboratory confirmed in isolated, intact, microperfused MTAL that the main basolateral bicarbonate efflux pathway was Cl Ϫ dependent, Na ϩ independent, and 4,4Ј-diisothiocyanostilbene-2,2Ј-disulfonic acid (DIDS) sensitive, properties shared with AE2 (16).…”
Section: Discussionmentioning
confidence: 83%
“…In two studies using basolateral membrane vesicles isolated from a purified MTAL tubule suspension, we previously demonstrated that the main basolateral HCO 3 Ϫ efflux pathway in MTAL cells is via Cl Ϫ /HCO 3 Ϫ exchange activity attributable to AE2 (12,13). An additional study from our laboratory confirmed in isolated, intact, microperfused MTAL that the main basolateral bicarbonate efflux pathway was Cl Ϫ dependent, Na ϩ independent, and 4,4Ј-diisothiocyanostilbene-2,2Ј-disulfonic acid (DIDS) sensitive, properties shared with AE2 (16).…”
Section: Discussionmentioning
confidence: 83%
“…Although the fractional inhibition by aldosterone was slightly lower in the presence of luminal DIDS, we are hesitant to ascribe any physiological significance to this because it is the result of an increase in basal HCO 3 Ϫ absorption rate observed when apical K ϩ -HCO 3 Ϫ cotransport is inhibited (39). Nevertheless, our results do not conclusively rule out that an effect of aldosterone to increase apical K Ϫ transport pathways (5,6,31). In keeping with its central role in the maintenance of sodium, volume, and acid-base balance, NHE3 is regulated acutely by several important factors, including catecholamines, angiotensin II, endothelin, dopamine, and growth factors (2,25,32,42).…”
Section: Fig 7 Inhibition Of Hcomentioning
confidence: 75%
“…Intracellular pH was monitored using the pH-sensitive dye BCECF (29). Intracellular dye was calibrated at the end of each experiment using the high-[K + ]/nigericin technique (48). Briefly, tubules were perfused and bathed with a HEPES-buffered, 95-mM K + solution containing 10 μM of the K + /H + exchanger nigericin.…”
Section: Methodsmentioning
confidence: 99%